Ultra-fast amorphization of crystalline alloys by ultrasonic vibrations. (10th April 2023) - Li, Luyao; Lyu, Guo-Jian; Li, Hongzhen; Fan, Caitao; Wen, Wenxin; Lin, Hongji; Huang, Bo; Sohrabi, Sajad; Ren, Shuai; Liang, Xiong; Wang, Yun-Jiang; Ma, Jiang; et al.
Highlights: A facile and rapid solid-state amorphization method was discovered. The tuning of amorphous content was achieved. Ultrasonic vibration method exhibits an outstanding time advantage than other methods. The elements redistribute uniformly and rapidly under ultrasonic vibration. A new order-disorder transition mechanism was introduced. Abstract: The amorphization of alloys is of both broad scientific interests and engineering significance. Despite considered as an efficient strategy to regulate and even achieve record-breaking properties of metallic materials, a facile and rapid method to trigger solid-state amorphization is still being pursued. Here we report such a method to utilize ultrasonic vibration to trigger amorphization of intermetallic compound. The ultrasonic vibrations can cause tunable amorphization at room temperature and low stress (2 MPa) conveniently. Remarkably, the ultrasonic-induced amorphization could be achieved in 60 s, which is 360 times faster than the ball milling (2.16 × 10 4 s) with the similar proportion of amorphization. The elements redistribute uniformly and rapidly via the activated short-circuit diffusion. Both experimental evidences and simulations show that the amorphous phase initiates and expands at nanograin boundaries, owing to the induction of lattice instability. This work provides a groundbreaking strategy for developing novel materials with tunable structures and properties.